Reforming Mining Governance in Indonesia’s National Strategic Projects: Lessons from Canada and Australia - A. Muhammad Hasgar A.S.; Adhe Ismail Ananda (CV. Cognispectra Publishing, 2026)
This study examines mining governance within Indonesia’s National Strategic Projects framework by comparing regulatory and institutional practices in Canada and Australia. It addresses the continuing gap between the acceleration of mineral-based development and the protection of environmental, social, and community interests. The research applies normative legal research through comparative and conceptual approaches. Legal materials are analysed using six criteria: institutional architecture, licensing and impact assessment, transparency, public and Indigenous participation, monitoring and enforcement, and mine closure. The findings show that Canada connects impact assessment with Indigenous rights, knowledge, and negotiated project obligations, while Australia combines federal environmental review, state mining authority, native title negotiation, and financial rehabilitation mechanisms. Both systems continue to face jurisdictional fragmentation, power imbalances, and inconsistencies in implementation. Indonesia possesses an extensive regulatory framework, but its effectiveness remains limited by fragmented coordination, formalistic participation, weak data integration, inconsistent enforcement, and inadequate post-mining accountability. This study proposes a contextualised mining governance model based on pre-design sustainability screening, integrated licensing, meaningful participation and benefit-sharing, and independent compliance monitoring. The model rejects direct legal transplantation and instead promotes the functional adaptation of comparative practices to Indonesia’s constitutional, administrative, and socio-ecological condition